The Transnational Mosque : Architecture and Historical Memory in the Contemporary Middle East - Rizvi, Kishwar (Book collections on Project MUSE., 2015)
"Kishwar Rizvi, drawing on the multifaceted history of the Middle East, offers a richly illustrated analysis of the role of transnational mosques in the construction of contemporary Muslim identity. As Rizvi explains, transnational mosques are structures built through the support of both government sponsorship, whether in the home country or abroad, and diverse transnational networks. By concentrating on mosques--especially those built at the turn of the twenty-first century--as the epitome of Islamic architecture, Rizvi elucidates their significance as sites for both the validation of religious praxis and the construction of national and religious ideologies"--